Local governments' indebtedness and its impact on real estate prices - Martin Micheli (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2016)
In this paper, we estimate the causal effect of public debt on real estate prices and rental prices. We identify shocks to investment credits of self-governed cities in Germany and control for potential benefits such as an increased supply of public goods, which might come in hand with increased indebtedness. Using spatial variation across self-governed cities allows us to estimate this effect. We find that shocks to public debt have a significant negative effect on apartment prices. Rental prices, on the other hand, do not seem to be affected by public debt. Tenants care more about the current and less about the future tax burden. – – In diesem Papier untersuchen wir den kausalen Effekt öffentlicher Verschuldung auf Immobilienpreise. Hierfür identifizieren wir zuerst Schocks der Investitionskreditposition kreisfreier Städte. Um für potenziell positive Effekte, welche mit einem Anstieg der öffentlichen Verschuldung einhergehen können, zu kontrollieren, nutzen wir den Standort der beobachteten Immobilien. Wir finden einen signifikant negativen Effekt öffentlicher Verschuldung auf Wohnungspreise. Für Wohnungsmieten finden wir keinen signifikanten Einfluss der Verschuldung. Mieten scheinen mehr von der aktuellen als von der zukünftigen Steuerbelastung abzuhängen.
Keywords: R30; R51; 330; real estate prices; local government debt